2006
DOI: 10.4049/jimmunol.177.2.1197
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Binding-Deficient Exotoxin Is a Potent Noninflammatory Broad Spectrum Intradermal Immunoadjuvant

Abstract: Intradermal (i.d.) immunization is a promising route of vaccine administration. Suitable i.d. adjuvants are important to increase vaccine efficacy in poorly responding populations such as the elderly or for dose-sparing strategies in the face of vaccine shortages. Bacterial exotoxins, such as Escherichia coli heat-labile enterotoxin (LT), exert strong immunostimulatory effects through binding to monosialoganglioside (GM1) cell surface receptors; however, injection is hampered by local inflammation. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 65 publications
3
30
0
6
Order By: Relevance
“…S8), effectively excluding this possibility. The EPI adjuvant properties of CT thus depend on the availability of the gangliosides capable of binding CT-B on host cells, in contrast to studies using intradermal delivery of CT and LT (30).…”
Section: Adjuvant Effects Of Ctmentioning
confidence: 88%
See 1 more Smart Citation
“…S8), effectively excluding this possibility. The EPI adjuvant properties of CT thus depend on the availability of the gangliosides capable of binding CT-B on host cells, in contrast to studies using intradermal delivery of CT and LT (30).…”
Section: Adjuvant Effects Of Ctmentioning
confidence: 88%
“…The A subunit displays ADP ribosylation activity, whereas the pentameric B subunit acts as a receptor for cell entry by high-affinity binding to GM1 ganglioside present at the cell surface (10-12) However, one study reported robust intradermal adjuvant activities of both CT and LT occur in the absence of GM1 binding (30), indicating alternative mechanisms through which CT may provoke the immune response. To determine whether the EPI adjuvant effects of CT require recognition of GM1, we utilized mice (GalT −/− ) deficient in the two glycosyltransferases involved in GM1 biosynthesis.…”
Section: Adjuvant Effects Of Ctmentioning
confidence: 99%
“…However, when delivered via the i.d. route, LT-I induced intense and persistent inflammatory reactions in mice (44). In contrast, no information is available for the inflammatory effects of LT-II enterotoxins, particularly LT-IIa, when they are administered by the i.d.…”
mentioning
confidence: 99%
“…For evaluation of cytokine production, spleen cells were harvested from animals euthanized 2 weeks after the immunization protocol (44). Spleen cells from mice of the same immunization group were pooled (1 ϫ 10 7 viable cells/ml) and cultured in a CO 2 -containing atmosphere at 37°C in the presence or absence of OVA (5 g/ml), the OVA class )-restricted CD4 ϩ T cell epitope synthetic peptide ( 265 TEWTSSNVMEERKIKV 280 , denoted OVA 265-280 ) (1.2 g/ml).…”
Section: Cloning Of Lt-iia and Lt-iiab 5 Subunit-encoding Genesmentioning
confidence: 99%
See 1 more Smart Citation